The experiences, needs and barriers of people with impairments related to usability and accessibility of digital health solutions, levels of involvement in the design process and strategies for participatory and universal design: a scoping review - Silje Havrevold Henni; Sigurd Maurud; Kristin Skeide Fuglerud; Anne Moen (BMC, 2022)
Abstract Objective Globally, the number of digital health solutions is increasing, but they are not always designed with access and utilisation for people with impairments in mind. Development efforts have often not included the voice and requirements of people with impairments, who make up 15% of the world's population, despite the fact that this can help ensure broad access and utilisation. Little attention to and limited inclusion of people with impairments in the development of digital health solutions results in continued and reinforced inequalities in health services provision for people with impairments. This review investigates the needs and barriers of people with impairments related to use of digital health solutions and strategies to foster user participation, access and utilisation of digital health solutions. Methods This scoping review, based on the Joanna Briggs Institute Manual, had five phases: 1) identification of aim and research questions, 2) literature search in five databases (April/May 2020), 3) literature screening based on predetermined inclusion and exclusion criteria, 4) data extraction, and (5) reporting results. Results The literature search resulted in 5968 sources, of which 25 met our inclusion criteria. People with impairments appreciate digital health solutions that are designed to meet their specific impairment-related challenges. The reported needs and barriers related to technological design varied depending on the individuals' challenges. The literature reported different types of participatory co-design strategies to foster access and utilisation of digital health solutions. Conclusion This scoping review support needs for increased awareness among developers to design solutions that meet people's needs, contexts and states of health. By applying universal design as a strategy and including people with different types of impairments, starting in the idea creation phase of digital health solutions and throughout the development, developers can design solutions with better accessibility. Digital health solutions that are accessible and usable have a tremendous opportunity to foster health equity and achieve health promotion, prevention and self-care. This in turn can contribute to closing the gap between different population groups, reduce disparities and get the most from available healthcare services.